2016
DOI: 10.1162/jocn_a_00987
|View full text |Cite
|
Sign up to set email alerts
|

Memory-reliant Post-error Slowing Is Associated with Successful Learning and Fronto-occipital Activity

Abstract: Abstract■ Negative feedback after an action in a cognitive task can lead to devaluing that action on future trials as well as to more cautious responding when encountering that same choice again. These phenomena have been explored in the past by reinforcement learning theories and cognitive control accounts, respectively. Yet, how cognitive control interacts with value updating to give rise to adequate adaptations under uncertainty is less clear. In this fMRI study, we investigated cognitive control-based beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 57 publications
(76 reference statements)
1
5
0
Order By: Relevance
“…Finally, more accurate future trials could be differentiated from less accurate trials through latent process components of the decision during the first post-error trial. This shows that even in the absence of a direct relation of RT and accuracy on the post-error trial, post-error adaptations could still be beneficial with regard to future trials, as has been previously observed (Schiffler et al, 2016). …”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…Finally, more accurate future trials could be differentiated from less accurate trials through latent process components of the decision during the first post-error trial. This shows that even in the absence of a direct relation of RT and accuracy on the post-error trial, post-error adaptations could still be beneficial with regard to future trials, as has been previously observed (Schiffler et al, 2016). …”
Section: Resultssupporting
confidence: 76%
“…This result illustrates how the post-error adaptation process may influence accuracy of future responses (Hester et al, 2007; Schiffler et al, 2016). Given that task-relevant neural activation increases and decreases have previously been found in relation to post-error adaptations (King et al, 2010; Danielmeier et al, 2011; Steinhauser et al, 2017), this finding is not surprising.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…It is worth mentioning that, although the discovery of post-error behaviors dates back from the 60s, current research is still very active in this domain and largely aimed, now, at identifying the brain structures that are targeted by post-error action monitoring processes (e.g., Danielmeier et al, 2015;Beatty et al, 2018; and also at identifying the brain mechanisms (e.g., Purcell and Kiani, 2016;Schiffler et al, 2016;Perri et al, 2017), brain structures (e.g., Schiffler et al, 2016;Zhang et al, 2017;Fu et al, 2019), or neurochemical systems (e.g., Danielmeier et al, 2015;Sellaro et al, 2015) that are involved in or responsible for post-error behaviors.…”
Section: What Does a Man/woman Do After He/she Makes An Error?mentioning
confidence: 99%